Primary rat hepatocytes in chemical testing and QSAR predictive applicability - Tichý, Miloň; Pokorná, Adéla; Hanzlíková, Iveta; Nerudová, Jana; Tumová, Jana; Uzlová, Rút (Toxicology in vitro, 2010)
Primary rat hepatocytes were used to test acute toxicities of 16 neutral aliphatic alcohols, ketones and esters. Their effects on cell viability and metabolic function (ureogenesis, i.e. biotransformation of ornithine to urea) were measured and expressed as EC50 values. Log EC50 values from both tests correlated with the log partition coefficients for the chemicals between n-octanol and water and log P(ow)-based QSAR models were derived. Log EC50 (viability) tightly correlates with log EC50 (ureogenesis): log EC50 (viability)=0.91 log EC50 (ureogenesis)+0.06. Each of these toxic indices can be substituted by the other one. The toxic indices for both cell viability and metabolic disorder can be estimated using log EC50 for movement inhibition in the oligochaete Tubifex tubifex and the respective QSAR equation. It eliminates a usage of rats. Their correlations were proved and justified.
Keywords: hepatocyty; trypanová modř; Animals; roztoky; Chemistry, Physical; vztah mezi dávkou a účinkem léčiva; Trypan Blue; Rats, Wistar; Toxicology; močovina; Quantitative Structure-Activity Relationship; Urea; Predictive Value of Tests; indikátory a reagencie; prediktivní hodnota testů; Coloring Agents; fyzikální chemie; kultivované buňky; Indicators and Reagents; Hepatocytes; Solutions; separace buněk; Cells, Cultured; Dose-Response Relationship, Drug; Male; barvicí látky; krysa rodu Rattus; Cell Separation; zvířata; mužské pohlaví; toxikologie; Rats; potkani Wistar; kvantitativní vztahy mezi strukturou a aktivitou